2018
DOI: 10.1155/2018/4692081
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Roles of Extracellular Vesicles in Cigarette Smoke‐Associated Diseases

Abstract: Cigarette smoke contains more than 4,500 chemicals; most of which are highly reactive free radicals, which induce proinflammatory and carcinogenic reactions. Numerous efforts have focused extensively on the role of cigarette smoking as a cause of many diseases. Extracellular vesicles and exosomes have recently received increasing interest for their diagnostic and therapeutic roles in many diseases. However, research done on the role of extracellular vesicles and exosomes on cigarette smoke-induced chronic dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 68 publications
(110 reference statements)
1
34
0
Order By: Relevance
“…CYP-mediated elevations in oxidative stress that accompany tobacco smoking, also promote HIV-1 replication [13,14,50,51]. Additionally, cigarette smoking is associated with EV release in smokers and in various cell types in vitro [96]. Our study revealed that EVs from CSC-treated cells were found to alter their antioxidant capacity and packaging-showing a protective effect against toxicity and viral replication in the early stages of HIV-1 replication [92].…”
Section: Tobacco Smoking and Ev Cyp2a6 1b1 1a1mentioning
confidence: 64%
“…CYP-mediated elevations in oxidative stress that accompany tobacco smoking, also promote HIV-1 replication [13,14,50,51]. Additionally, cigarette smoking is associated with EV release in smokers and in various cell types in vitro [96]. Our study revealed that EVs from CSC-treated cells were found to alter their antioxidant capacity and packaging-showing a protective effect against toxicity and viral replication in the early stages of HIV-1 replication [92].…”
Section: Tobacco Smoking and Ev Cyp2a6 1b1 1a1mentioning
confidence: 64%
“…Indeed, miRNA overload activates TL3 receptors in lymphocytes triggering cytokine production, protease release, leukocytes recruitment and inflammation [79]. Release of extracellular vesicles plays a pathogenic role in the lung damage induced by cigarette smoke [80]. miRNAs themselves also contribute to inhibition of methylation of CpG sites.…”
Section: Epigenetic Factors In the Development Of Cancermentioning
confidence: 99%
“…Cigarette smoke induced release of exosomes may be involved in the progression of chronic diseases (25,26). Also, the role of exosomes release by cigarette smoke extract have been implicated in altering cellular functions such as endothelial dysfunction and in ammatory conditions (26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%